Diversity and specificity of arbuscular mycorrhizal fungi in the rhizosphere of six plants in the Songnen grassland, China. Issue 1 (2nd January 2020) - Bi, Yu; Ma, Wenjun; Xing, Fu; Gao, Ying; Li, Zhuo; Chen, Chen; Mu, Xuemeng; Li, Xiaote; Zhu, Xinrui
ABSTRACT: Arbuscular mycorrhizal fungi (AMF) are widely distributed in grassland ecosystems. However, the diversity and specificity of AMF in the rhizosphere of grassland plants remain largely unexplored. The species and quantitative characteristics of AMF in the rhizosphere soil of 6 common plant species in the Songnen grassland in Northeast China were investigated by using wet sieving and morphological identification methods. The results showed that there were 24 AMF species belonging to 6 genera in the rhizosphere of the 6 plant species. Glomus claroideum and Glomus melanosporum were the common dominant AMF species for most plants. The subdominant species and companion species of the AMF community were different. The diversity index, spore density and infection rate of AMF were significantly different among the rhizosphere of the different plants ( p <  0.05). Similarity coefficients of AMF composition varied greatly among plant species. Therefore, the AMF species showed a certain level of host specificity, and this result partially supported the singular hypothesis. Differences in plant species and soil microenvironment were the main reasons explaining the specificity of the AMF in the rhizospheres of grassland plant species.